Which conflicts can the European neighbourhood policy help resolve? - Thorvaldur Gylfason; Per Magnus Wijkman (Center for Economic Studies and ifo Institute (CESifo), 2012)
Under what conditions can the European Neighbourhood Policy achieve one of its main objectives: to resolve conflicts in the European Union's neighbourhood? In the spirit of Montesquieu and Monnet, the basic hypothesis of the EU is that closer economic integration encourages governments to take steps to resolve conflicts and vice versa, creating a virtuous circle of prosperity and detente. The EU has a strong motive in this, since conflicts in its neighbourhood spill-over into the EU itself. The paper identifies some factors important for success, including the existence of active facilitators of compromise, strong intraregional trade, and the prospect of accession to the EU. It concludes that the EU's Member States must give conflict resolution greater priority in the European Neighbourhood Policy and provide stronger means, larger resources and better incentives if this goal is to be realised.
Keywords: F13; F15; 330; trade; Balkans; European Neighbourhood Policy; Außenpolitik; Wirtschaftsintegration; Europäische Integration; Friedenssicherung; EU-Staaten; Europa